Poor College Students’ Resilience Phase in Online Learning during the Covid-19 Pandemic - Irawan, Andi Wahyu; Muslifar, Rury; Dwisona, Dwisona (Jurnal Kajian Bimbingan dan Konseling, 2021)
After a year of the Covid-19 pandemic, online learning remains to be carried out in Indonesia. In this situation, college students have to survive with excellent resilience amid various restraints. This study investigates the poor college students’ resilience phase in online learning during the Covid-19 pandemic. With the qualitative inquiry narrative method, this study involved 30 college students from Universitas Mulawarman as the participants. The participants were selected through the purposive sampling technique and interviewed via phone call. The analysis process was carried out using the induction and deduction process, while the analysis was completed based on the field data and referred to the theory in the deduction process. The research results show that college students experience three resilience phases in online learning: survival, adaptation, and recovery. The survival stage occurs in the initial months of online learning, while the adaptation phase occurs in the first six months of online learning. From the tenths month of online learning, students have reached the recovery stage. Following this research finding, guidance and counseling services in the universities are required to facilitate poor students to enhance their survivability during this pandemic.